Performing rurality. But who? - Dymitrow Mirek; Brauer Rene (Bulletin of Geography. Socio-Economic Series, 2017)
Reflective inquiries to better understand ‘the rural’ have tried to embed rural research within the notion of performativity. Performativity assumes that the capacity of language is not simply to communicate but also to consummate action, whereupon citational uses of concepts produce a series of material effects. Of late, this philosophical shift has also implicated geographers as active agents in producing, reproducing and performing rurality. This paper provides a critical evaluation of what this new insistence really means for the production of geographical knowledge. Using framework analysis as a method, the paper scrutinizes several reportedly influential papers on the topic of rural performativity. Our findings reveal that, while indeed reflexive on issues of academic integrity, methodology and ethics, performances of rurality are continuedly placed ‘out there’ amongst ‘rural people’, i.e. in a priori defined and often stereotypically understood contexts, either by way of ‘spatial delimitation’ or ‘activity delimitation’. Effectively, such testimonies provide a truncated state of fidelity, where performance- oriented reflexivity is seconded by contradictory empirics of uneven value and with few commonalities. We conclude that by turning towards performativity as an allegedly more helpful way of obtaining rural coherence, we at the same time overlook our own role in keeping ‘rural theory’ alive.